13C‐metabolic flux analysis of human adenovirus infection: Implications for viral vector production. Issue 1 (9th August 2016) - Carinhas, Nuno; Koshkin, Alexey; Pais, Daniel A.M.; Alves, Paula M.; Teixeira, Ana P.
ABSTRACT: Adenoviruses are human pathogens increasingly used as gene therapy and vaccination vectors. However, their impact on cell metabolism is poorly characterized. We performed carbon labeling experiments with [1, 2‐ 13 C]glucose or [U‐ 13 C]glutamine to evaluate metabolic alterations in the amniocyte‐derived, E1‐transformed 1G3 cell line during production of a human adenovirus type 5 vector (AdV5). Nonstationary 13 C‐metabolic flux analysis revealed increased fluxes of glycolysis (17%) and markedly PPP (over fourfold) and cytosolic AcCoA formation (nearly twofold) following infection of growing cells. Interestingly, infection of growth‐arrested cells increased overall carbon flow even more, including glutamine anaplerosis and TCA cycle activity (both over 1.5‐fold), but was unable to stimulate the PPP and was associated with a steep drop in AdV5 replication (almost 80%). Our results underscore the importance of nucleic and fatty acid biosynthesis for adenovirus replication. Overall, we portray a metabolic blueprint of human adenovirus infection, highlighting similarities with other viruses and cancer, and suggest strategies to improve AdV5 production. Biotechnol. Bioeng. 2017;114: 195–207. © 2016 Wiley Periodicals, Inc. Abstract : Human adenovirus 5 vectors (AdV5) are widely explored for gene therapy and vaccination, but their impact on cellular metabolism is poorly described. Through parallel 13 C labelling and metabolic flux analysis, the authors quantified the impact of AdV5 infection on exponentially growing and growth‐arrested human cells. The results show the cellular state before infection significantly affects the metabolism—AdV5 interplay, and highlight the pentose phosphate—pathway and lipid precursor generation as potential upregulation targets for optimization of adenoviral vector production processes.